Transmittivity of a disordered superlattice with the scatterers inside barriers in the external electric field - Korol, Anatoliy (My University, 1995)
In this work the tunneling spectra of a disordered semiconductor superlattice (SL) in the presence of external electric field are evaluated.
Keywords: disordered superlattice; electric field; transmittivity; невпорядкована надгратка; трансмісійність; електричне поле; электрическое поле; трансмиссионность; неупорядоченная сверхрешетка; кафедра фізики та професійної безпеки